Pemanfaatan Potensi Kopi Dan Rempah-Rempah Pada Inovasi Produk Untuk Meningkatkan Perekonomian Masyarakat Desa - Agti Pribatiwi; Syevila Ukhriawati M; Irvan Nur Ridho (AMMA : Jurnal Pengabdian Masyarakat, 2024)
Coffee is a type of plantation crop that has been around for a long time and has been cultivated and has high value.  Ponorogo Regency, especially Ngrayun Village, is a large coffee producer. This village has large human resource potential with the main livelihood being gardening. The majority of residents in Ngrayun Village have a lot of free time to produce raw coffee into processed coffee. However, most of the coffee production is still sold in the form of coffee cherries, so sales results are still not optimal. The solution offered to this problem is to process coffee into spiced coffee. Spiced coffee is prepared by processing coffee beans into coffee powder and adding various types of spices such as ginger, cardamom, cinnamon, mango ginger, cloves and turmeric to enhance the taste. The aim of this activity is to increase coffee bean innovation and the use of coffee beans to obtain a higher selling value.